Direct-writing of organic field-effect transistors on plastic achieving 22 MHz transition frequency. (6th August 2020) - Passarella, Bianca; Scaccabarozzi, Alberto D; Giorgio, Michele; Perinot, Andrea; Marina Barbier, Sara; Martìn, Jaime; Caironi, Mario
Abstract: Organic field effect transistors are considered among the key enablers of flexible, wearable, lightweight and portable electronics. The possibility to fabricate polymer-based devices from solution with high throughput processes makes organic electronics suitable for low cost mass-production of new and diverse applications. Nevertheless, the investigation of the dynamic behaviour of these devices, i.e. their operational frequency, is still limited and the reported operational speed remains low, especially on flexible substrates, limiting their applicability in many circuitry applications. In this work, we report downscaled p-type polymer field effect transistors (FETs), fabricated on both rigid and flexible polymer substrates, by a combination of coating and direct-writing techniques, achieving radio-frequency operation. FETs with the shortest channel of 1.2 µ m can operate up to 22 MHz at a relatively low bias voltage of −12 V, as measured by scattering parameters. Such a transition frequency ( f T ) is the highest so far recorded for organic transistors fabricated on flexible substrates. In terms of fT normalized by the applied gate-to-source voltage ( fT / V GS ), the achieved 1.83 MHz V −1 is the highest for solution-processed organic transistors on plastic. This result paves the way to the implementation of polymer radio-frequency devices with cost-effective fabrication processes on flexible substrates.